2018
DOI: 10.3390/coatings8110385
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Hydrogen Free Diamond-Like Carbon Thin Films Deposited by High Power Impulse Magnetron Sputtering with Ne

Abstract: Hydrogen-free diamond-like carbon (DLC) thin films are attractive for a wide range of industrial applications. One of the challenges related to the use of hard DLC lies in the high intrinsic compressive stresses that limit the film adhesion. Here, we report on the mechanical and tribological properties of DLC films deposited by High Power Impulse Magnetron Sputtering (HiPIMS) with Ne as the process gas. In contrast to standard magnetron sputtering as well as standard Ar-based HiPIMS process, the Ne-HiPIMS lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The coating fills the micro-grooves on the surface, thereby providing a kind of "healing" of the surface (it should be noted that a similar effect is observed when applying coatings of various compositions). There is reason to expect that the coating will affect the characteristics of ceramic samples taking into account the described effect and the fact that the hardness of the formed DLC coating is not less than 25 GPa [73][74][75][76][77], which significantly exceeds the initial hardness of the tool ceramics, and the coating has a lower coefficient of friction and good strength of the adhesive bond with ceramic basis [78][79][80].…”
Section: Influence Of Dlc Coatings On the Transformation Of The Sintered Ceramic Blanks Characteristicsmentioning
confidence: 99%
“…The coating fills the micro-grooves on the surface, thereby providing a kind of "healing" of the surface (it should be noted that a similar effect is observed when applying coatings of various compositions). There is reason to expect that the coating will affect the characteristics of ceramic samples taking into account the described effect and the fact that the hardness of the formed DLC coating is not less than 25 GPa [73][74][75][76][77], which significantly exceeds the initial hardness of the tool ceramics, and the coating has a lower coefficient of friction and good strength of the adhesive bond with ceramic basis [78][79][80].…”
Section: Influence Of Dlc Coatings On the Transformation Of The Sintered Ceramic Blanks Characteristicsmentioning
confidence: 99%
“…The main goal was to obtain hard coatings with low friction coefficients and wear rates, and with smooth surface. Two main approaches were followed and combined for tuning the process: (i) addition of Ne into the gas mixture, in order to improve the C ionization [18,34] and (ii) use of acetylene to increase the deposition rate through the contribution of C atoms from decomposition of gas precursor [10,35].…”
Section: Process Descriptionmentioning
confidence: 99%
“…Since Ne has higher ionization energy than Ar, 21.56 eV, and 15.5 eV, respectively [14], with the introduction of Ne in the deposition plasma, it is possible to increase the temperature of the electrons and the ionization fraction of the ionized carbon species. Several researchers have reported that the mixture of gases in the plasma atmosphere, Ar + Ne, or even the total replacement of Ar by Ne resulted in significant improvements in the mechanical and tribological properties of DLC coatings [15,16].…”
Section: Introductionmentioning
confidence: 99%